European Union’s Securitization and Favoritism Phenomenon: Lesson Learned from the 2015 Europe’s Migrant Crisis - Firsty Chintya Laksmi Perbawani (WIMAYA, 2022)
This research article aims to portray the phenomenon of how Europe’s perspective and attitudes toward migration. Race, culture, and politics all play a prominent role in Europe’s reception of migrants. This article precisely focused on the role of the European Union (EU) during the 2015 migrant crisis. As Europe faced the struggle where 1.3 million refugees and migrants illegally entered Europe by the sea in 2015, compared to roughly 200,000 in 2014. The author argues that European countries have responded to the issue discordly, with some welcoming migrants and others rejecting them. This article founds the reasons, namely: (1) securitization within the EU, i.e., raising the issue of migration as a “matter of European security”; and (2) the phenomenon of favoritism, as evidenced by selective solidarity, racism, and anti-immigrant rhetoric. This article attests that both securitization and favoritism culture in Europe must be recalculated and used as lessons learned so that there is no bias in allowing forthcoming migrants and so that the EU continues to exist.